Acute Effects of Ketamine on Intracranial Pressure in Children With Severe Traumatic Brain Injury*. Issue 5 (21st February 2023) - Laws, Jennifer C.; Vance, E. Haley; Betters, Kristina A.; Anderson, Jessica J.; Fleishman, Sydney; Bonfield, Christopher M.; Wellons, John C.; Xu, Meng; Slaughter, James C.; Giuse, Dario A.; Patel, Neal; Jordan, Lori C.; et al.
Abstract : OBJECTIVES: The acute cerebral physiologic effects of ketamine in children have been incompletely described. We assessed the acute effects of ketamine on intracranial pressure (ICP) and cerebral perfusion pressure (CPP) in children with severe traumatic brain injury (TBI). DESIGN: In this retrospective observational study, patients received bolus doses of ketamine for sedation or as a treatment for ICP crisis (ICP > 20 mm Hg for > 5 min). Administration times were synchronized with ICP and CPP recordings at 1-minute intervals logged in an automated database within the electronic health record. ICP and CPP were each averaged in epochs following drug administration and compared with baseline values. Age-based CPP thresholds were subtracted from CPP recordings and compared with baseline values. Trends in ICP and CPP over time were assessed using generalized least squares regression. SETTING: A 30-bed tertiary care children's hospital PICU. PATIENTS: Children with severe TBI who underwent ICP monitoring. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We analyzed data from 33 patients, ages 1 month to 16 years, 22 of whom received bolus doses of ketamine, with 127 doses analyzed. Demographics, patient, and injury characteristics were similar between patients who did versus did not receive ketamine boluses. In analysis of the subset of ketamine doses used only for sedation, there was no significant difference in ICP or CPP from baseline. Eighteen ketamine doses were given during ICP crises in 11 patients. ICP decreased following these doses and threshold-subtracted CPP rose. CONCLUSIONS: In this retrospective, exploratory study, ICP did not increase following ketamine administration. In the setting of a guidelines-based protocol, ketamine was associated with a reduction in ICP during ICP crises. If these findings are reproduced in a larger study, ketamine may warrant consideration as a treatment for intracranial hypertension in children with severe TBI.